Intergenerational learning among teachers: overt and covert forms of continuing professional development. Issue 3 (27th May 2017) - Brücknerová, Karla; Novotný, Petr
Abstract : This article interprets data from qualitative research into intergenerational learning (IGL) among teachers at Czech primary and secondary schools. The objective of the text is to answer the question: ʻWhat are teachers of different generations learning from one another in schools and in what ways does this learning take place?' Drawing on a framework adapted from Illeris, we perceive the basic principle of learning as content acquisition through interaction. Therefore, our answer has the form of an overview of forms of content (acceptable specific item, acceptable aggregate, challenging specific item, challenging aggregate, complex challenge) and forms of interaction (perception, experience, transmission, participation, perception). The data were collected through 22 interviews with teachers. The analysis employs selected procedures based in grounded theory. This allowed us to define four types of IGL: adopting IGL, transformative IGL, exploratory IGL and inspiration-taking IGL. This typology is discussed regarding its usefulness for understanding and planning teachers' continuing professional development.